2018
DOI: 10.1111/jfd.12779
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of xanthine oxidase inhibition with the antioxidant property of nanoencapsulated Melaleuca alternifolia essential oil in fish experimentally infected with Pseudomonas aeruginosa

Abstract: Nanoencapsulated Melaleuca alternifolia essential oil (tea tree oil, TTO) is a natural alternative treatment, with 100% therapeutic efficacy in fish experimentally infected with Pseudomonas aeruginosa, and has also potent protective effects linked with antioxidant properties. However, the pathways responsible for the antioxidant capacity remain unknown. Thus, this study evaluated whether the inhibition of seric xanthine oxidase (XO) activity can be considered a pathway involved in the antioxidant capacity of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It is therefore imperative that existing antibiotics be used more thoughtfully. In this regard, natural compounds with intrinsic antimicrobial potential such as polyphenols, alkaloids, or sulfur-containing compounds [ 9 , 10 , 11 ] as well as essential oils (EOs) [ 12 , 13 , 14 ] have been proposed as a viable complement to fight the problem of antibiotic resistance. Several studies reported that, due to the complexity of their chemical constituents, EOs are able not only to exhibit powerful antimicrobial activity but also to act in synergy when simultaneously used with conventional antibiotics, therefore enhancing their antimicrobial efficacy [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore imperative that existing antibiotics be used more thoughtfully. In this regard, natural compounds with intrinsic antimicrobial potential such as polyphenols, alkaloids, or sulfur-containing compounds [ 9 , 10 , 11 ] as well as essential oils (EOs) [ 12 , 13 , 14 ] have been proposed as a viable complement to fight the problem of antibiotic resistance. Several studies reported that, due to the complexity of their chemical constituents, EOs are able not only to exhibit powerful antimicrobial activity but also to act in synergy when simultaneously used with conventional antibiotics, therefore enhancing their antimicrobial efficacy [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%